Vulnerability for STD/HIV/AIDS: knowledge, attitudes and practices of adolescentes (Research, Society and Development, 2020)
This article objective to identify adolescentes of knowledge, attitudes and practices regarding vulnerability to STD/HIV/AIDS. This is a quantitative study, with a sample consisting of 1088 young students aged between 15 and 18 years. Data were obtained using a structured form, analyzed by SPSS software version 20.0. The results show that most of the participants had adequate knowledge about the ways of transmission of STD, with information on the topic received at school. However, many were unaware of the term vulnerability, although they considered themselves vulnerable to STD/HIV/AIDS. They demonstrated inappropriate attitudes and practices, especially by not using condoms in all sexual relations. There was a strong association between gender and having sex or not; gender and knowledge about vulnerability; having a partner and using other contraceptive methods; and between the beginning of sexual life with sexual orientation. Thus, the attitudes and practices referred to, especially the low use of condoms, require continuous encouragement for dialogue about safe behaviors, as they seem to be much more concerned with unwanted pregnancies than with the acquisition of sexually transmitted diseases.